Poly(Lactic Acid) Filled with Cassava Starch-g-Soybean Oil Maleate - Nopparut Kiangkitiwan; Kawee Srikulkit (The Scientific World Journal)
Poly(lactic acid), PLA, is a biodegradable polymer, but its applications are limited by its high cost and relatively poorer properties when compared to petroleum-based plastics. The addition of starch powder into PLA is one of the most promising efforts because starch is an abundant and cheap biopolymer. However, the challenge is the major problem associated with poor interfacial adhesion between the hydrophilic starch granules and the hydrophobic PLA, leading to poorer mechanical properties. In this paper, soybean oil maleate (SOMA) was synthesized by grafting soybean oil with various weight percents of maleic anhydride (MA) using dicumyl peroxide (DCP) as an initiator. Then, SOMA was employed for the surface modifying of cassava starch powder, resulting in SOMA-g-STARCH. The obtained SOMA-g-STARCH was mixed with PLA in various weight ratios using twin-screw extruder, resulting in PLA/SOMA-g-STARCH. Finally, the obtained PLA/SOMA-g-STARCH composites were prepared by a compression molding machines. The compatibility, thermal properties, morphology properties, and mechanical properties were characterized and evaluated. The results showed that the compatibility, surface appearance, and mechanical properties at 90 : 10 and 80 : 20 ratios of PLA/SOMA-g-STARCH were the best.